Potensi Pengolahan Buah Nangka Menjadi Marmalade di RT 03 Desa Buluh Rampai - Adelina Adelina; Nur Anisa; Nurma Enjelita; Fatmariani Fatmariani; Ichsan Yoga Pratama; Mia Meilina; Tria Susiawati; Melly Anggraini; Indah Fatmala; Lukman Hakim; Aldi Sebastian (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2023)
Jackfruit is a fruit that is quite common in RT 03 Buluh Rampai Village. The lack of utilization of jackfruit in RT 03 in its processing is still not optimal so it is necessary to innovate in processing jackfruit into a food that is liked by the wider community and can maintain the product's shelf life. One method of processing jackfruit that can maintain the product's shelf life is marmalade. Marmalade is a semi-solid snack in the form of a gel with the main ingredients namely sugar, pectin and pieces of fruit. The purpose of this field activity is to provide education about understanding the benefits and effectiveness of jackfruit in being transformed into an innovative, renewable product, namely marmalade. The working procedure approach in this activity includes the initial stages of observation, socialization and implementation. The result obtained is that the community can utilize jackfruit in a renewable processed product, namely marmalade products. Marmalade products produced through this training can be used as a product innovation development by the community, so that later the community can develop and increase micro, small and medium enterprises (MSMEs) in Buluh Rampai village for diversification.